THE EFFECT OF GREEN ECONOMY AND LOCAL WISDOM-BASED ENTREPRENEURIAL INNOVATION ON THE INCOME OF WEAVING MSMES IN SOUTHWEST SUMBA REGENCY - Alexander Adis; Karolus Wulla Rato (JTH: Journal of Technology and Health, 2026)
The primary objective of this study is to examine the impact of the green economy and local wisdom-based entrepreneurial innovation on the revenue of weaving MSMEs in Southwest Sumba Regency. Employing a quantitative approach with an explanatory research design, this study observes local handwoven fabric artisans. From the existing population, a sample of 45 business operators was selected using a purposive sampling technique. Primary data were gathered via Likert-scale questionnaires and subsequently analyzed using multiple linear regression. Field findings demonstrate that implementing a green economy—through eco-friendly raw materials, resource efficiency, waste reduction, and sustainable product creation—positively boosts income. Concurrently, innovation rooted in local heritage drives revenue growth by exploring traditional motifs, preserving authentic weaving techniques, embedding cultural values, utilizing local narratives, and strengthening product identity. Simultaneously, both aspects play a crucial role in enhancing competitiveness, profitability, and business sustainability. These final outcomes prove that accelerating weaving MSMEs relies not merely on product quality, but on strategic vision that merges environmental preservation with the power of local cultural roots.